Understanding unfolding and refolding of the antibody fragment (Fab). I. In-vitro study - Gani, Kayanat; Bhambure, Rahul; Deulgaonkar, Prashant; Mehta, Deepa; Kamble, Manoj (Biochemical Engineering Journal, 2020)
In-vitro protein refolding is a major rate-limiting step in the large scale production of antibody fragments expressed using a microbial source like E. coli. This investigation is focused on understanding the in-vitro unfolding and refolding of the multi-domain protein involving inter-domain disulfide linkage, like antibody fragment (Fab). Solubilization behavior of the inclusion bodies and unfolding events of Fab fragment (Biosimilar rHu Ranibizumab) were studied using nano-differential scanning fluorimetry (nano-DSF). Fab unfolding behavior was studied by fitting experimental data with the two-state and three-state thermodynamic model. Based on the Fab unfolding understanding, a two-stage design of experiment (DoE) strategy was used for the optimization of the in-vitro refolding condition of a Fab fragment. Refolding yield of 56.03 +/- 1.15 % was achieved using the optimized oxidative refolding conditions maintained by appropriate dilution factor and redox reagent ratio. Refolding kinetics of the rHu Ranibizumab was analyzed using a three-parameter kinetic model showing rate constant k(1) :7.05e(-6) l/mg.min, k(2) :0.57 l/mg.min, and k(3) :310.19 l/mg.min. Based on observed refolding kinetics, it was concluded that the Fab refolding follows a three-state mechanism with the refolding intermediate/(s) formation from light and heavy chain of the Fab fragment as an overall rate-limiting step. The method described here is a useful tool to identify high-yield scalable refolding conditions for multi-domain proteins involving inter-domain disulfide bonds.
Keywords: Antibody fragment; In-vitro refolding; Refolding kinetics; rHu Ranibizumab; Two-state and Three-state models

Mechanistic modeling of continuous capture step purification of biosimilar monoclonal antibody therapeutic - Deulgaonkar, Prashant; Bhambure, Rahul; Prasad, Bhaskarjyoti; Mishra, Ashok; Tiwari, Sanjay; Mody, Rustom (Journal of Chemical Technology and Biotechnology, 2022)
{BACKGROUND Continuous multicolumn Protein A chromatography offers various advantages for capture stage purification of monoclonal antibody therapeutics, like higher productivity and resin capacity utilization, lower buffer consumption, small footprint, etc. Due to the complexity of the continuous process, experimental optimization is time-consuming and cost-intensive. This investigation proposes a hybrid process development approach integrating experimental and mechanistic modeling for time- and cost-effective development and optimization of continuous Protein A affinity chromatography. RESULTS Productivity and capacity utilization of the continuous CaptureSMB process under varying operating conditions were predicted using the Chromatography Analysis and Design Toolkit (CADET) framework and validated with experimental results. Effects of critical process parameters like feed concentration (c(0)), loading breakthrough (s) and residence time (RT) on productivity and capacity utilization were evaluated. Model predictions were validated using the experimental results proving the reliability and feasibility of the modeling approach. At 15.00 +/- 0.20 mg mL(-1) feed model mAb concentration, the model-based approach predicted the best performance giving 27.56 g L-1 h(-1) productivity (RT = 2 min
Keywords: CaptureSMB; continuous chromatography; Mathematical modeling; Protein A; simulation